On some classes of four dimensional regular matrices - Sever, Yurdal; Altay, Bilal (My University, 2016)
In 1981, Rath and Tripathy presented some classes of regular matrices such that every bounded sequence is limitable by some member of each class of ordinary conservative matrices using ordinary sequences. The goal of this paper is to present multidimensional analogues of their results.
Keywords: Double Sequence; Regular Matrix; Matrix Class